My bridges of hope : searching for life and love after Auschwitz - Jackson, Livia Bitton (Simon & Schuster Books for Young Readers, 1999)
In 1945, after surviving a harrowing year in Auschwitz, fourteen-year-old Elli returns, along with her mother and brother, to the family home, now part of Slovakia, where they try to find a way to rebuild their shattered lives